MODIFICATION OF NATURAL ZEOLITE FROM CIKALONG WEST JAVA WITH HEXADECIL TRIMETIL AMMONIA AND ABSORPTION RATE TEST OF SULPHATE AND CHROMATE IONS - Husaini Husaini; Trisna Soenara (Institut Teknologi Bandung, 2003)
Cikalong mordenit natural zeolite with the average of cation exchange capacity (CEC) 154,2 meq/100 g has been used on modification trial. This modification attempts to increases the rate of anions absorbtion of zeolite in solution. On this research, zeolite is modificated using HDTMA through stirring process on beaker glass. Before the modification start, zeolite is set on pH 5 using sodium acetate solution. Variables on this research are: zeolite size (